Aprendizaje manufacturero, dependencia tecnológica y crecimiento económico: el caso colombiano - Ortiz Quevedo, Carlos Humberto; Vásquez Castro, Lina Marcela (Sociedad y Economía, 2007)
On the basis of a historical rationale about economic development, this paper contends that learning-by-doing in the manufacturing industrial sector, structural change and technological autonomy are mutually reinforced and impinge positively and significantly on economic growth. Time series from the Colombian national accounts are used to test this hypothesis